An Implementation and Evaluation of a Home Automation System Using Multi-Sensor Integration - Arslan, Muhammad; Qureshi, Muhammad Abdullah Arif; Sarwar, Umair (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The integration of home automation systems has become increasingly prevalent, driven by advancements in sensor technologies and microcontroller capabilities. This paper presents the design, implementation, and evaluation of a comprehensive home automation system utilizing various sensors and control mechanisms. The system includes motion detectors, thermal sensors, presence sensors, light sensors, and devices such as fans and lighting systems. The effectiveness of the system in enhancing energy efficiency, comfort, and convenience is evaluated based on its real-world performance. Keywords Home Automation, Sensor Integration, Energy Efficiency, Temperature Control, Lighting Management